2020
DOI: 10.1186/s40673-020-0111-8
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal cerebellar volume in somatic vs. non-somatic delusional disorders

Abstract: Background: There is abundant evidence for cerebellar involvement in schizophrenia, where the cerebellum has been suggested to contribute to cognitive, affective and motor dysfunction. More recently, specific cerebellar regions have also been associated with psychotic symptoms, particularly with auditory verbal hallucinations. In contrast, little is known about cerebellar contributions to delusions, and even less is known about whether cerebellar involvement differs by delusional content. Methods: Using struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…To investigate between-group differences, voxel-wise t tests were calculated. As in previous studies [ 35 , 36 ], given a strong a priori hypothesis, we chose a significance threshold of p < 0.005 (uncorrected at the voxel level) to assess between-group differences. Based on random field theory [ 37 ], an empirically determined extent threshold according to the expected number of voxels per cluster within the respective contrast was applied.…”
Section: Methodsmentioning
confidence: 99%
“…To investigate between-group differences, voxel-wise t tests were calculated. As in previous studies [ 35 , 36 ], given a strong a priori hypothesis, we chose a significance threshold of p < 0.005 (uncorrected at the voxel level) to assess between-group differences. Based on random field theory [ 37 ], an empirically determined extent threshold according to the expected number of voxels per cluster within the respective contrast was applied.…”
Section: Methodsmentioning
confidence: 99%
“…The third hypothesis was that poor response to treatment in DD in old age would be associated with brain changes and/or cognitive defects. Several of the studies we reviewed point to the presence of neurobiological correlates of delusions (cerebellar abnormalities [20], alterations in gray and white matter, lacunar infarctions and ischemic brain lesions in DD [19,22,29,30]. Our literature search suggests, but does not prove, that brain lesions can impair the response to psychotropic medications in the elderly age group [20].…”
Section: Discussionmentioning
confidence: 90%
“…Krämer et al [20] carried out a brain-imaging study in 14 patients with DD somatictype, 18 patients with nonsomatic DD, 18 patients with schizophrenia (SZ) and 32 healthy controls. Cerebellum-optimized segmentation images were obtained by MRI.…”
Section: Relationship Of Brain Structure Cognition and Treatment Resp...mentioning
confidence: 99%
“…Higher GMV in the bilateral lobule VIIa/crus II has been detected in patients with somatic-type delusional disorder than in those with non-somatic delusional disorder. Patients with schizophrenia also showed increased GMV in VIIa/crus I compared with HC ( Krämer et al, 2020 ). Task-based fMRI confirmed that crus I is activated by executive functions such as working memory, planning, organizing, and strategy formation.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, sex differences in GMV may account for the inconsistency; the proportion of men among SD patients in the study is only 4/25. The SUIT toolbox offers a high-resolution, spatially unbiased template of the human cerebellum, enabling more accurate intersubject alignment than whole-brain methods (Krämer et al, 2020). In some cases, SUIT is more sensitive to cerebellar changes than conventional whole-brain VBM (Diedrichsen, 2006;Kühn et al, 2012).…”
Section: No Clusters Survivedmentioning
confidence: 99%